A Fast Room Temperature NH3 Sensor Based on an Al/p-Si/Al Structure with Schottky Electrodes - Suwan Zhu; Xiaolong Liu; Jun Zhuang; Li Zhao (Sensors, 2017)
In this paper, an electrical-based NH3 sensor with an Al/p-Si/Al structure is reported. The p-Si substrate is microstructured by fs-laser irradiation and then etched by 30% alkaline solution. This sensor works well at room temperature with fast response/recovery for NH3 gas at 5–100 ppm concentration. However, when the sensor is annealed in N2/H2 forming gas or short-circuited for Al/Si electrodes, its sensitivity decreases drastically and almost vanishes. Further I-V and FT-IR results show that the two back-to-back Schottky diodes on the device play a key role in its sensing performance.